King Lear - Shakespeare, William 1564-1616 (United Kingdom : Sweet Cherry Publishing Limited, 2015)
An ageing king makes a capricious decision to divide his realm among his three daughters according to the love they express for him. When the youngest daughter refuses to take part in this charade, she is banished, leaving the king dependent on her manipulative and untrustworthy sisters.
Primary
800-899
Keywords: Lear, King of England (Legendary character); Britons -- Juvenile literature; Fathers and daughters -- Juvenile literature; Inheritance and succession -- Juvenile literature; Kings and rulers -- Juvenile literature; Aging parents -- Juvenile literature